Does FDI contribute to technological spillovers and growth? : a panel data analysis of Hungarian firms - Bosco, Maria Giovanna (2001)
Questions whether foreign affiliates perform better than local firms; if there are spillovers from foreign affiliates to domestic firms; and whether the presence of foreign affiliates in high-technology industries enhances technological spillovers.